Role of Actors in the Processes of Sustainable Development at Local Level—Experiences From the Czech Republic - Dlouhá, Jana; Vávra, Jan; Pospíšilová, Marie; Dvořáková Líšková, Zuzana (Frontiers in Sustainability, 2022)
In this text we are interested in the preconditions for, and opportunities provided by sustainable development at local level in non-metropolitan areas, i.e. in rural areas and villages. These areas are generally seen as having an important role in achieving sustainability. The literature review highlights the general principles of endogenous development with an emphasis on local resources including human potential and social capital, and the Czech context. In practice, the empowerment and cooperation of regional actors is crucial for the sustainable transition of rural areas; an analysis of the local situation was thus conducted from the perspective of social capital. Research primarily questioned the role of local actors in different areas related to sustainable development, their relationships and involvement in sustainability processes, as well as deficiencies in social conditions creating barriers to sustainable development. The research methods selected to answer these questions reflected the context-specific, scientifically-overlooked character of the theme of this research where emerging phenomena were at the centre of our interest. A survey conducted with representatives of the National Network of Local Action Groups mapped the situation in 50 (out of 180) LAGs in CR. Data were analysed quantitatively (single and multiple-choice questions), in combination with qualitative methods which were used to transform and aggregate responses into conceptual categories which were monitored for frequency (to observe majority opinion). The diversity of local actors, their relationships and roles in the sustainable development processes was thus illustrated. A snapshot of actors’ current involvement in specific areas of sustainable development was compared with their potential involvement in these areas illustrating the importance of social capital which is not always recognized in relevant policy documents. The engagement of these diverse actors in sustainability transition processes is less evident: in most of the categories of change, the role of public administration prevails. According to the respondents, these changes that would ensure a sustainable future of the regions are often not taking place. While some of these findings may be specific to geographically-defined regional conditions and the Czech historical context, the research raised theoretically relevant questions concerning the role of social capital sustainability processes.